Early versus delayed invasive strategy in patients with non-ST-elevation acute coronary syndrome and concomitant congestive heart failure. Issue 4 (October 2019) - Yoshida, Ruka; Ishii, Hideki; Morishima, Itsuro; Tanaka, Akihito; Morita, Yasuhiro; Takagi, Kensuke; Yoshioka, Naoki; Hirayama, Kenshi; Iwakawa, Naoki; Tashiro, Hiroshi; Kojima, Hiroki; Mitsuda, Takayuki; et al.
Highlights: Early intervention for non-ST elevation acute coronary syndrome (NSTE-ACS) with congestive heart failure (CHF) significantly prevented adverse cardiac events. The benefit of early intervention was mainly observed in patients needing ventilators. The risk of bleeding and acute kidney injury were higher in the early invasive group. Most NSTE-ACS patients with CHF revealed advanced coronary artery disease. Abstracts: Background: Although there are guidelines that recommend an early invasive strategy in patients with non-ST-elevation acute coronary syndrome (NSTE-ACS) and concomitant congestive heart failure (CHF), optimal timing of the invasive strategy remains controversial. Methods: Among 2045 patients who were admitted owing to NSTE-ACS or CHF, 300 presented with NSTE-ACS and concomitant CHF. Of the 300 patients, we enrolled 160 patients for whom coronary angiography (CAG) during their hospital stay was planned at the time of admission; 64 of these patients were classified into the early invasive group (<24 h) and 96 were classified to the delayed invasive group (≥24 h). We evaluated the primary outcome which was defined as a composite of cardiac mortality, life-threatening arrhythmia, and non-fatal myocardial infarction (MI). Results: The median time between presentation and CAG was 2 h in the early invasive group and 240 h in the delayed group. During follow-up, the primary outcome was significantly lower in the early invasive group [hazard ratio (HR), 0.52; 95% confidence interval (CI), 0.30–0.87; p  = 0.01]. After the adjustment of confounding factors, the primary outcome was significantly less frequent (HR, 0.44; 95% CI, 0.23–0.78; p  = 0.004) in the early invasive group compared to the delayed invasive group. Conclusions: The early invasive strategy was associated with a lower risk of the composite primary outcome in the long-term follow-up of patients with NSTE-ACS and concomitant CHF.